KEANEKARAGAMAN JENIS BURUNG DIURNAL PADA KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG DI DESA SUNGAI DERAS KABUPATEN KUBU RAYA KALIMANTAN BARAT - darno, Su; Said, Syafruddin; anto, Eri (Universitas Tanjungpura, 2014)
Wildlife is one of the natural resources that have an important role in human life both in terms of ecology, recreation, economy, tourism,education and science. Extinction of birds in nature means the loss of natural resources by human presence is very valuable because it is where the bird needs to be preserved. The purpose of this study was to determine the diurnal bird species diversity in the area of ??Mount Ambawang fores Protected in sungai deras village of Kubu Raya district of West Kalimantan. Based on observations indicate that the path of the three habitats in the number of birds diurnal observations obtained at the study site 31 species . 17 habitats types encountered In Primary Forests with 740 individuals. In the 15 species encountered in secondary forest region with 568 individuals and 13 species encountered habitats About Rice fields with 735 individuals. The result of the calculation is known that the greatest dominance for the morning and afternoon there at about rice field early morning with a value of C = 0.1491 C = 0.1404 afternoon and evening there is a dominance index in secondary forest with a value of C = 0.1490 afternoon . The highest species diversity for each time of observation found in primary forest with morning values ??h = 1.1578 , p = 1.1777 and h during the afternoon = 1.2859. Similarity of the highest found in the forest area of ??the district Forest Primary Secondary with value = 43.75 % IS morning , noon IS and IS = 56.25 % = 62.50 % afternoon. Keyword: Diversity, bird, diurnal, forest preserve, mount Ambawang.